Search for lepton-flavour-violating decays of the Higgs and $Z$ bosons with the ATLAS detector - ATLAS collaboration (2846 authors) (2019)
Submitted by Helmut Wolters (helmut@coimbra.lip.pt) on 2019-02-04T09:51:50Z No. of bitstreams: 2 1.pdf: 709509 bytes, checksum: f1e2d1a9fd7a96a011d9800273a3c8d5 (MD5) zip/1452557.zip: 560226 bytes, checksum: d452f98b632ca36b688f65d8c44cf91e (MD5)